The effect of abiotic factors to nutrient and physical parameters changes at man-made lake and natural lake: a case study in Kota Kinabalu city, Sabah - Haris, Nurnajihatul Afiqah Anum (2020)
This study on the effect of abiotic factors to nutrient and physical parameters changes at man-made and natural lake at Kota Kinabalu City, Sabah. To archive the aim of this study there are few concentration of nutrient and physical parameter were determine namely Nitrogen-Ammonia, Nitrite, Silica, pH value, dissolve oxygen and temperature at Perdana Park Lake and Tun Fuad Stephen Lake, Kota Kinabalu, Sabah. The comparison between the parameter at both lakes with the evaluation of the effect of abiotic factors to nutrient and physical parameters changes at Perdana Park Lake and Tun Fuad Stephen Lake. 5 area of stations are selected at each lake with 3 replicates of each. Water physico-parameter namely pH value, Dissolve Oxygen (mg/l), Temperature (°C), were measured in situ by using Hanna, HI9298194 Multiparameter while chemical-parameter namely Nitrogen-Ammonia, Nitrite and Silica were measured by Spectrophotometer brand Hach model DR2800 in laboratory. Overall, the range of nutrient level at man-made lake as follows; Nitrogen-Ammonia (0.157 – 0.328), Nitrite (0.0212 – 0.0192), Silica (9.740 – 12.420), pH (7.24 – 8.254), dissolve oxygen (2.220 – 4.260), and temperature (28.91 – 30.26). While the range of nutrient level at natural lake are Nitrogen-Ammonia (0.207 – 0.388), Nitrite (0.0110 – 0.140), Silica (3.32 – 6.26), pH (6.488 – 7.282), dissolve oxygen (2.286 – 4.502) and temperature (29.16 – 31.01). From the statistical analysis, there are difference of physical parameter between 2 lakes where for pH (p<0.021), DO (p<0.033) and temperature (p<0.025). It show that the human activities, natural process or weather fluctuation that affected it. From correlation testing, abiotic factors give positive and negative correlation to the nutrient and physical parameters changes. For humidity, the nitrogen-ammonia and pH showed positive correlation (rs=0.330, p<0.002), (rs=0.231, p<0.028) while dissolved oxygen showed negative correlation (rs=-0.264, p<0.012) to the abiotic factors. For temperature, only the dissolve oxygen showed positive correlation (rs=0.280, p<0.008) to the abiotic factors. In addition, nitrogen-ammonia and nitrite showed positive correlation (rs=0.417, p<0.000), (rs=0.281, p<0.007) to physical parameter like pH. Further studies on water quality research and maintenance of health relationship between aquatic ecosystem and physico-chemical properties of water needed to be implement to avoid the major problem in the future.